Speaking the Gospel - Leushuis, Reinier (Erasmus studies, 2016)
In his Paraphrases on the synoptic gospels, Erasmus stages the voice of the evangelist speaking in the first-person singular to address the reader in the second-person singular. Such a marked interlocutorial setting is absent in Scripture, with the exception of Luke’s brief address to a certain Theophilus. More than a strategy to forestall criticisms directed at the author of the paraphrase, this direct engagement between biblical author and reader reveals a deeper concern for the transfer of gospel faith and gospel philosophy to the minds of his contemporaries. This essay examines the ways in which the evangelist’s voice engages the implied reader in the Paraphrases on Matthew, Luke, and most notably Mark. It focuses on the reliability (fides) of narration and narrator, the emotional, sensory, and homiletic engagement between speaking voice and reader, and the role of drama and performative elements. The paraphrastic staging of the evangelist’s voice reflects each gospel’s unique challenge in conveying Philosophia Christi to the reader and in the Paraphrase on Mark illustrates in particular the literary dimension of reader-oriented imitatio.